Effect of reflux time in the esterification of kapok fibre for used cooking oil (UCO) treatment: article - Samsuddin, Noor Zalina; Alias, Nor Halaliza (2018)
In the process of food preparation, used cooking oil (UCO) is produced as a waste. It is an edible oil that classified into vegetable oil which has been used in food making process. One of the applications of UCO is that it can be converted into biodiesel. Nevertheless, it can lead to another problem such as blockages of sewer pipes if being discharged down into kitchen sinks. Thus, a few practical treatments have been conducted to solve the problem such as alkaline-catalyzed transesterification. However, none of the treatments could reduce the environmental impacts as it contains high free fatty acid that has made the reaction not efficient. Hence, the aim of this research is to find the alternative method to reduce the oil content in UCO before discharging into the river by using kapok fibre. Kapok fibre is natural plant fibre that can be renewed. The kapok fibre was investigated for adsorptive removal of oil in UCO. Hydrophobicity of this adsorbent was improved via esterification process in the presence of stearic acid and calcium oxide as catalyst. The effect of reflux time was studied on the esterification of kapok fibre. Both of modified and unmodified kapok fibre were prepared to compare the oil adsorption towards UCO. In the esterification reaction, kapok fibre was mixed stearic acid in the ratio of 1:1, with the percentage catalyst of 10 wt% of kapok fibre mass and refluxing time were tested at 1, 2 and 4 hours, respectively. The experiments were repeated in duplicates. From the results, the average oil removal efficiency produced at 1 and 2 hours were 31.25% and 32.85%, respectively. Meanwhile, the highest oil removal efficiency was obtained at 34.21% by using refluxing time at 4 hours. The unmodified kapok fibre gave the lowest oil removal efficiency compared to modified kapok fibre (MKF) which is at 25.85%.